2012
DOI: 10.5223/pghn.2012.15.4.256
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Pharmacological Treatment in Pediatric Nonalcoholic Fatty Liver Disease

Abstract: PurposeWith growing number of obese children, the prevalence of nonalcoholic fatty liver disease (NAFLD) in pediatric population is increasing. Nonalcoholic steatohepatitis (NASH) is a severe form of NAFLD, and can cause morbid complications. It is important to identify patients in order to grade pathologic severities and treat those children who possibly have NASH. This study was performed to evaluate whether the pharmacological therapy is also effective as well as the body weight reduction in pediatric NAFLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The authors recommended that the primary recommendation should be the BMI reduction, however pharmacological treatment plus BMI reduction could have a more therapeutic effect in this children with NAFLD. Although Urso administration without BMI reduction did not demonstrate any improvement in disease process (1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors recommended that the primary recommendation should be the BMI reduction, however pharmacological treatment plus BMI reduction could have a more therapeutic effect in this children with NAFLD. Although Urso administration without BMI reduction did not demonstrate any improvement in disease process (1).…”
Section: Discussionmentioning
confidence: 99%
“…A body mass index (BMI) reduction combined with vitamin E and ursodeoxycholic acid (UDCA) showed a significantly higher rate of improvement in a clinical profiles study of 29 children and demonstrated that the first-line therapy should consist of BMI reduction (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations